The Jerusalem Question and Its Resolution: Selected Documents - Hirsch, Moshe,; Lapidoth, Ruth, (International Law - Book Archive pre-2000., 1994)
It is universally accepted that Jerusalem is a unique city. It stirs up strong emotions among adherents of various religions as it is the centre of three religions, and it is the subject of conflicting national aspirations of two peoples. The diverse attitudes and wishes associated with the city are expressed, inter alia , in certain documents. This collection presents the most important of these documents. This will help the reader to understand the difficulties and may assist in the search for solutions. There may be differences of opinion over historical facts and documents may be subject to differing interpretations. Convenient access to the relevant documents is a prerequisite for any attempt to understand the problem and seek solutions. The collection includes documents concerning the status of Jerusalem from the point of view of Israel's law and administration, as well as documents from the Arab world and from the international sphere. The editors have focused on official documents and in particular on those that have had a practical influence on the status of the city, or are likely to do so in the future. The collection will assist students and scholars who seek to understand the special status of Jerusalem, as well as politicians and diplomats who are responsible for ensuring its welfare and prosperity.